Early fasting glucose measurements can predict later glycaemic response to once weekly dulaglutide. Issue 3 (21st July 2015) - Grunberger, G.; Forst, T.; Fernández Landó, L.; Pechtner, V.; Shaginian, R.; Jia, N.; Gough, S.
Abstract: Aims: To assess whether early measures of fasting blood glucose predict later glycaemic response with once‐weekly dulaglutide in patients with Type 2 diabetes mellitus. Methods: Post hoc analyses were conducted separately for two phase 3 studies (AWARD–5 and AWARD–1) in patients assigned to once‐weekly dulaglutide. Week 2 fasting blood glucose was used as a predictor variable, and glycaemic treatment response was defined by HbA1c response based on a composite efficacy endpoint. The association between fasting blood glucose and the glycaemic response was analysed using chi‐square tests. Results: There was a strong association between fasting blood glucose < 7.9 mmol/l at week 2 and achieving the HbA1c composite efficacy endpoint at week 26 ( P  < 0.01). Higher fasting blood glucose at week 2, however, did not predict absence of glycaemic response and requires further assessment. Conclusions: Fasting blood glucose measured at 2 weeks may be an early and useful predictor of glycaemic response to once‐weekly dulaglutide treatment. What's new?: Although dulaglutide is a weekly glucagon‐like peptide–1 receptor agonist, these results demonstrated that early fasting blood glucose measurements can predict later glycaemic response to its treatment. These data suggest that early fasting blood glucose measurement may provide useful information for clinicians wishing to follow an individualized patient‐centred approach.